Nursing care in the emergency service for women victims of violence (Research, Society and Development, 2021)
Objective: to identify in the scientific literature the care provided by Nursing professionals in the Emergency Service to women who are victims of violence. Method: integrative review, carried out in the VHL, MEDLINE/PubMed, SciELO and CINAHL databases, in April and May 2021. Results: from the sample of 17 articles, it was perceived five horizontal perspectives: the care provided by nurses to women victims of violence; repairing damage caused to health; the social impacts of violence against women; the increase in violence against women in the pandemic and, finally, strategies to combat violence against women. Conclusion: Nursing care is characterized by its various functionalities which can constitute strategic tools for the health of women victims of domestic violence in the context of public health, highlighting the need to build multidisciplinary teams.